A STUDY OF BENEFIT AND COST ANALYIS OF THE COMPOSTING AND THERMAL DECOMPOSITION FOR ORGANIC WASTE MANAGEMENT - Raden Arief Firmansyah; Khoirul Hidayat (Universitas Darussalam Gontor, 2023)
Awareness of Indonesian people about waste management is low, specifically in organic waste management. Organic waste management is relatively easy. On the other hand, the community or person always chooses open dumping and open burning. These techniques are not sustainable actions, for the environment, even for living things. Waste could be managed sustainably, i.e., composting and thermal decomposition (pyrolisis). Composting produces organic fertilizer that is saleable and profitable. Thermal decomposition (pyrolysis) potentially have three product, bio-oil, bio-char, and syngas. These products are marketable and promising too. This research aims to study the potential application of composting and thermal decomposition technology on a small-neighborhood scale based on cost-benefit analysis. The study used benefit-cost analysis. Literature studies collect data from national and international journals, law products, and government policies. The study resulted that composting required more area than pyrolisis. It is a constraint criterion to consider applying the composting method in TPS 3R. The social cost green house gas (GHG) was the biggest component that contributed to the total cost. Meanwhile, in total benefit, the benefit sale of product solid waste treatment was the biggest. Pyrolisis was more feasible than composting based on BCR value. The composting duration was the limiting factor that affected the BCR value negatively (less than 1). It indicated to sustainable running, TPS 3R should be subsidized on investment and operational costs. Composting should be applied at the household level to achieve the maximal benefit. Sharing responsibilities between the household level and TPS 3R management about percentage of processing organic waste should be implemented. It could level out household participation in solid waste management.